Comparative analysis of fungal communities between herbicide-resistant and -susceptible Alopecurus aequalis - Zhan, You; Liu, Haozhe; Cao, Ziheng; Chen, Wen; Li, Zongfang; Bai, Lianyang; Pan, Lang (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction Alopecurus aequalis is a grass species invading Chinese canola and wheat fields. An A. aequalis KMN-R population surviving mesosulfuron-methyl treatment with recommended rates was acquired from wheatland. Here, we aimed to confirm the resistance profiles of KMN-R to acetolactate synthetase (ALS) inhibiting herbicides and explore the possible resistance mechanisms to mesosulfuron-methyl in this weed population. Methods The dose-response tests performed in our study were used to test the toxicity of A. aequalis to ALS-inhibiting herbicides. Sanger sequencing was used to analyze the ALS gene of mesosulfuron-methyl -resistant and -susceptible A. aequalis. RNA sequencing analysis was used to find candidate genes that may confer metabolic resistance to the mesosulfuron-methyl in resistant A. aequalis population. Mesosulfuron-methyl -resistant and -susceptible A. aequalis populations fungal composition was measured via Illumina MiSeq Sequencing. Results Dose-response results indicated that KMN-R population evolved resistance to mesosulfuron-methyl and other tested ALS-inhibiting herbicides. Known resistance-conferring Trp-574-Leu gene mutation in A. aequalis ALS was detected in the KMN-R population. Pretreatment with 4-chloro-7-nitrobenzoxadiazole reversed mesosulfuron-methyl resistance in KMN-R. Glutathione S-transferases (GST) gene GSTZ2 and GSTT3 were highly expressed in KMN-R population. In addition, we evaluated the alpha diversity in A. aequalis, centering on OTU abundance, equality, and multiplicity, and found that the fungal community composition had more unexplained variance between KMN-R and KMN-S A. aequalis. We also observed higher abundances of specific fungi in KMN-R A. aequalis. Discussion The results proved that resistance to mesosulfuron-methyl in A. aequalis KMN-R population is probably caused by target site- and non-target site-based relating GST and provided the basis for further research between fungal interaction and herbicide resistance.